The effect of tree decline over soil water content largely controls soil respiration dynamics in a Mediterranean woodland - Rodríguez, Alexandra (2023)
As drought-induced tree defoliation and mortality (i.e. tree decline) in the Mediterranean with ongoing climate change, it is of paramount importance to understand how, why, and when tree decline affects soil respiration (Rs). We carried out a novel study exploring the interacting effects of climatic variability (i.e. season and year) and tree decline on soil water content (SWC), soil temperature (Tsoil), and Rs temporal variability in a Mediterranean holm oak woodland. The study further explores the effects of tree decline on the main controls of Rs at the stand scale (i.e. plant variables, SWC, Tsoil, and soil physicochemical variables). We monitored Rs, Tsoil, and SWC under the canopy of 30 holm oak trees with different defoliation degrees (healthy, affected, and dead) during two years of contrasting precipitation patterns. We estimated different plant structural variables (e.g. height, canopy diameter) on those selected trees under whose canopies we also collected soil samples to analyze different soil physicochemical variables. Our study provides, up to our knowledge, the first observational (i.e. in situ) evidence that tree decline might decrease the positive response of Rs to increased precipitation and drying-rewetting cycles. It also suggests that tree decline can significantly increase SWC and decrease Rs but largely depending on the declining stage, the year, and the season. Finally, tree decline affected the relative importance of the different drivers of Rs, with both SWC and Tsoil gaining importance as trees defoliate and die. Altogether, our results point towards a negative impact of drought-induced tree decline on soil carbon (C) content and cycling, particularly under forecasted climate change scenarios with dryer and more intense precipitation regimes.